1993
DOI: 10.1029/93ja02282
|View full text |Cite
|
Sign up to set email alerts
|

Limb view spectrum of the Earth's airglow

Abstract: Sometimes the Earth's airglow layer, when observed in the limb view, appears to be a double layer. During one of these occasions we were able to obtain absolute spectral intensity and altitude profiles for most well‐known airglow features from the space shuttle on the STS‐37 mission. The lower of the two airglow layers consisted of the OH Meinel bands, the ground state of the O2 atmospheric band at 762 nm and an intense nighttime sodium layer at 598 nm peaking near 92 km. The upper airglow layer consists of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 32 publications
2
31
0
Order By: Relevance
“…Mende et al (1993) presented another study addressing the question, whether OH emissions from higher vibrational levels occur at higher altitudes. The authors used measurements taken with a grating spectrometer flown on the space shuttle (mission STS-37) in November 1990.…”
Section: Comparison To Previous Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mende et al (1993) presented another study addressing the question, whether OH emissions from higher vibrational levels occur at higher altitudes. The authors used measurements taken with a grating spectrometer flown on the space shuttle (mission STS-37) in November 1990.…”
Section: Comparison To Previous Resultsmentioning
confidence: 99%
“…Furthermore, the main results of these studies are partly contradictory. Some model (McDade, 1991) and experimental studies (Mende et al, 1993) indicate that differences in emission peak altitudes for different vibrational levels are rather small. Other model (Makhlouf et al, 1995;Adler-Golden, 1997;Baker and Stair, 1988;Xu et al, 2012) and experimental results (Kaufmann et al, 2008;Xu et al, 2012) suggest a vibrational level dependence of the emission peak altitude of several km.…”
Section: Introductionmentioning
confidence: 99%
“…The heights of the 557.7-nm and 630.0-nm emission layers are generally thought to be about 110 km and 250 km, respectively (Sahai et al, 1990;Mende et al, 1993;Shepherd et al, 1995), but Vallance Jones et al (1991) reported that the peak height of 557.7-nm emission is about 125 km. Reflecting the uncertainty of the precise height of measurement, we shall refer to the 630.0-nm measurements as upper thermospheric winds and to the 557.7-nm measurements as lower thermospheric winds.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The image reveals two distinct emission layers centered at different altitude levels. The upper emission is due to the OI( 1 D) airglow emission layer and the lower emission is due to the OH(9,3) airglow emission layer (Burnside et al 1977;Mende et al 1993). Rajesh et al (2009) suggested that most of the OH(9,3) enhancements observed by ISUAL were the result of the line-of-sight integration of the corresponding OI( 1 D) enhancements.…”
Section: Instrumentation and Observationsmentioning
confidence: 99%